Hematopoietic and leukemic stem cells homeostasis: the role of bone marrow niche - Shaimaa Khattab; Manal El Sorady; Ashraf El-Ghandour; Giuseppe Visani; Pier Paolo Piccaluga (Open Exploration Publishing Inc., 2024)
The bone marrow microenvironment (BMM) has highly specialized anatomical characteristics that provide a sanctuary place for hematopoietic stem cells (HSCs) that allow appropriate proliferation, maintenance, and self-renewal capacity. Several cell types contribute to the constitution and function of the bone marrow niche. Interestingly, uncovering the secrets of BMM and its interaction with HSCs in health paved the road for research aiming at better understanding the concept of leukemic stem cells (LSCs) and their altered niche. In fact, they share many signals that are responsible for interactions between LSCs and the bone marrow niche, due to several biological similarities between LSCs and HSCs. On the other hand, LSCs differ from HSCs in their abnormal activation of important signaling pathways that regulate survival, proliferation, drug resistance, invasion, and spread. Targeting these altered niches can help in better treatment choices for hematological malignancies and bone marrow disorders in general and acute myeloid leukemia (AML) in particular. Moreover, targeting those niches may help in decreasing the emergence of drug resistance and lower the relapse rate. In this article, the authors reviewed the most recent literature on bone marrow niches and their relations with either normal HSCs and AML cells/LSC, by focusing on pathogenetic and therapeutic implications.